Rational Use of Intravenous Fluids in Critically Ill Patients - Malbrain, Manu L.N.G; Wong, Adrian; Nasa, Prashant; Ghosh, Supradip (Springer International Publishing : Imprint: Springer, 2024)
This open access book, published by Springer under the Open Access CC BY 4.0 Licence in collaboration with the International Fluid Academy (IFA, www.fluidacademy.org), explores rationalized intravenous fluid therapy for critically ill patients. Despite being commonly prescribed in inpatient settings, intravenous fluids are often administered without evidence-based guidelines, neglecting essential considerations such as the fact they are drugs, that need proper dosing, duration, indications, contraindications, side effects, and de-escalation. This book fills this knowledge gap. Each chapter starts with a clinical vignette and a related question, followed by a concise summary abstract, key learning points, main text, and a conclusion that addresses the clinical question and provides relevant take-home messages. Additionally, every chapter includes an IFA commentary referencing the latest literature and evidence. The book begins with an introductory chapter that provides definitions and terminology, followed by four sections. The first section covers the fundamentals of intravenous fluid therapy, including fluid compartments in sick patients, fluid bolus dynamics, heart-lung interactions, fluid challenge, fluid responsiveness, arterial blood gas analysis based on traditional and Stewart concepts, and electrolyte physiology relevant to clinical issues. The second section discusses commercially available intravenous fluids, while the third section focuses on fluid therapy in specific clinical situations. The final section introduces the concepts of fluid stewardship and appropriate fluid prescription. Aligned with the International Fluid Academy's mission to enhance education and promote research on fluid management and monitoring, ultimately improving patient survival rates, this book contributes significantly to establishing fluid stewardship at the bedside. It provides valuable support for physicians, nurses, pharmacists, and other healthcare professionals across various clinical disciplines working in emergency rooms, operating rooms, or intensive care units, aiding their everyday clinical practice.